Annihilation Mechanism of Low-Angle Grain Boundary in Nanocrystalline Metals - Guofeng Zhou; Qishan Huang; Yingbin Chen; Xiongqing Yu; Haofei Zhou (Metals, 2022)
Due to the high density of grain boundaries (GBs), nanocrystalline metals possess superior properties, including enhanced strength, work hardening, and fatigue resistance, in comparison to their conventional counterparts. The expectation of GB migration is critical for grain coarsening and GB annihilation in these materials, significantly affecting the polycrystalline network and mechanical behavior. Here, we perform molecular dynamics (MD) simulations on gold (Au) nanocrystals containing multiple parallelly arranged GBs, with a focus on the investigation of annihilation mechanisms of low-angle grain boundaries (LAGBs). It is observed that the shear-coupled motion of LAGBs, consisting of dislocations, gives rise to their preliminary migration with the reduced separation distance between GBs. With subsequent GB motion, the LAGBs encountered with neighboring GBs, and can be annihilated by various mechanisms, including dislocations interpenetration, dislocations interaction, or dislocations absorption, depending on the specific configuration of the neighboring GB. These findings enhance our understanding of GB interactions and shed light on the controlled fabrication of high-performance nanocrystalline metals.